1999
DOI: 10.1136/bjo.83.7.779
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and keratometric astigmatism up to 1 year following small flap trabeculectomy (microtrabeculectomy)

Abstract: In the 1990s a number of authors have studied the refractive changes induced in the cornea as a result of the procedure.2-6 Several surgical modifications have been described, [7][8][9][10][11] each of which may theoretically influence the changes noted in the cornea following surgery. In 1995 we reported the intraocular pressure results following microtrabeculectomy, a small flap modification of the original design which we have utilised routinely since 1991.11 The scleral trapdoor at 2 × 2 mm is approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 13 publications
(12 reference statements)
1
36
0
4
Order By: Relevance
“…82 The size of the incision appears to be correlated to the amount of induced astigmatism with smaller incisions (as used in 'microtrabeculectomy' procedures) leading to a smaller astigmatic change. 80 The exact cause of the corneal change following trabeculectomy is not known, although it has been postulated that it relates to tension from sutures used in the surgery, 82 cauterisation of the wound 80,82 or wound healing factors 79 leading to steepening of the cornea in the superior meridian.…”
Section: Astigmatism Resulting From Ocular Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…82 The size of the incision appears to be correlated to the amount of induced astigmatism with smaller incisions (as used in 'microtrabeculectomy' procedures) leading to a smaller astigmatic change. 80 The exact cause of the corneal change following trabeculectomy is not known, although it has been postulated that it relates to tension from sutures used in the surgery, 82 cauterisation of the wound 80,82 or wound healing factors 79 leading to steepening of the cornea in the superior meridian.…”
Section: Astigmatism Resulting From Ocular Surgerymentioning
confidence: 99%
“…76 Most studies have noted these corneal changes to be transient 74,77,78 but significant change can persist up to six months following surgery. 75,76 Trabeculectomy for glaucoma can cause significant corneal change, which is typically a steepening in the vertical meridian, leading to an increase in regular WTR [79][80][81] and irregular astigmatism. 82 The size of the incision appears to be correlated to the amount of induced astigmatism with smaller incisions (as used in 'microtrabeculectomy' procedures) leading to a smaller astigmatic change.…”
Section: Astigmatism Resulting From Ocular Surgerymentioning
confidence: 99%
“…These results were on eyes which had a 4x3 mm scleral trap door with two 10/0 nylon sutures. Vernon et al (1999) reported in a study of small flap (2mm x 2mm sclera trap door and o.75 mm internal sclerotomy) trabeculectomy procedure performed at the 90 degrees meridian on 16 eyes with the use of 10-0 nylone suture. By vector analysis, the mean surgically induced refractive changes (SIRC) in cylinder power vectors induced at 1, 3, 6, and 12 months as measured by manual keratometry were 0.68, 0.38, 0.52, and 0.55 dioptres, and by keratography 0.75, 0.66, 0.59, and 0.64 dioptres.…”
Section: Discussionmentioning
confidence: 99%
“…18 Trabeculectomy using a small scleral flap appears to provide medium to long-term IOP control comparable to large flap techniques 12,15,19 and may offer potential advantages: reduced surgical tissue trauma, a larger area of undisturbed sclera and conjunctiva should repeat surgery be required, and reduced astigmatism induction. 20 Potential disadvantages include possible decreased control over aqueous flow, technical challenges including difficulty in dissecting a large treatment area for antimetabolite application and difficulty in controlling subconjunctival bleeding if the conjunctival incision is small. Larger scleral flaps might give better tissue apposition over the scleral bed, and may give better IOP control.…”
Section: Introductionmentioning
confidence: 99%